2015
DOI: 10.1128/jcm.03424-14
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Peptide Nucleic Acid-Based Multiprobe Real-Time PCR Method Targeting the hsp65 Gene for Differentiation among Mycobacterium abscessus Strains

Abstract: c Recently, the need to distinguish between members of the Mycobacterium abscessus group has gained increasing attention. Here, we introduced a novel peptide nucleic acid (PNA) real-time PCR method targeting the hsp65 gene in order to distinguish between four subspecies within the M. abscessus group (M. abscessus and 3 types of M. massiliense).T he taxonomic status of the Mycobacterium abscessus group remains undetermined. The recent development of genetic investigation tools has revealed that the M. abscessus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Notably, the T m s measured from sputum samples showed small decreasing shifts (1–2.7 °C) compared to our previously reported T m s of clinical isolates of the M. abscessus genotypes [ 22 ] without compromising the discrimination of the genotypes. This outcome may be due to the presence of PCR-inhibitory substances in the DNA extracts from the sputum specimens because inhibitory substances can cause T m shifts [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Notably, the T m s measured from sputum samples showed small decreasing shifts (1–2.7 °C) compared to our previously reported T m s of clinical isolates of the M. abscessus genotypes [ 22 ] without compromising the discrimination of the genotypes. This outcome may be due to the presence of PCR-inhibitory substances in the DNA extracts from the sputum specimens because inhibitory substances can cause T m shifts [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 55%
“…In a previous study, we developed an hsp65 PNA RT-PCR targeting three signature SNPs in the 604-bp hsp65 gene that enabled the separation of the four types of M. abscessus ( M. abscessus and three types of M. massiliense ) at the cultured isolate level. The intra-genotypic conservation and inter-genotypic variation for each SNP of members of the M. abscessus group were confirmed by successful separation in 227 out of 228 clinical isolates (99.6 %) [ 22 ]. In this study, the application of the hsp65 PNA RT-PCR method to sputum samples demonstrated that this method could directly identify members of the M. abscessus group at the subspecies or genotypic level from sputum samples with 96.7 % sensitivity (29/30 samples) and 100 % specificity (Table 2 ), thereby demonstrating its feasibility in identifying the M. abscessus group not only from cultured isolates but also directly from sputum samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations